Review: The invasion of Acacia nilotica in Baluran National Park, Indonesia, and potential future control strategies - Shafia Zahra; RICHARD W. HOFSTETTER; KRISTEN M. WARING; CATHERINE GEHRING (Society for Indonesian Biodiversity, 2020)
Abstract. Zahra S, Hofstetter RW, Waring KM, Gehring C. 2020. Review: The invasion of Acacia nilotica in Baluran National Park, Indonesia, and potential future control strategies. Biodiversitas 21: 104-116. Acacia nilotica, commonly called prickly acacia, is infamous for its ability to invade various ecosystems, especially savannah. The tree was introduced to Baluran National Park (BNP), Indonesia in 1969 and nowadays has invaded more than 50% of BNP savannah habitat. Its presence has had significant negative impacts on local flora and fauna of the park. Physical and chemical eradication efforts of this plant have been conducted in the park but these have failed. Little is known about the tree invasion in Indonesia and no control suggestions have previously been proposed. Here, we review the causes and history of the invasion of this tree, describe previous attempts to eradicate the tree, and provide possible containment and control strategies. We describe 12 strategies based on successes and failures to control this tree in Indonesia and other countries and divide the methods into four categories: (i) physical: girdling the trunk, uprooting with winch, manual seedling uprooting, defloration, and restoration with fire; (ii) chemical: using biochar or herbicides; (iii) biological: using native plant competitors (grasses, shade trees), predators (insect) and pathogens (fungi) or microorganisms; (iv) social: centralized tree utilization, education outreach, and stakeholder collaboration. We summarize the relative effectiveness and efficiency of each method and explain how to integrate the aforementioned methods to help authorities choose the most appropriate strategies for their resources, needs and goals.